2018
DOI: 10.1159/000494346
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Opioid Antagonist Naloxone on Experimentally Induced Craving in Nicotine-Dependent Individuals

Abstract: Objective: Preclinical and clinical findings suggest a substantial association of the endogenous opioid system in nicotine dependence. The present study investigates the possible dose-dependent influence of naloxone, an unspecific opioid-receptor-antagonist, combined with cue exposure on the physiological state, locomotor activity, craving and the hypothalamic-pituitary-adrenal axis in nicotine-dependent humans. Methods: Twenty nicotine-dependent, outpatient participants were deprived of nicotine for over 4 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To date, it is unknown which non‐CB 2 receptor mechanisms are responsible for BCP‐induced reductions in nicotine or food self‐administration. Among potential non‐CB 2 receptor targets are fatty acid amide hydrolase (FAAH; Chicca et al, ), the major eCB degrading enzyme (Chicca et al, ), μ opioid receptors(Katsuyama et al, ; Paula‐Freire, Andersen, Gama, Molska, & Carlini, ), and peroxisome proliferator‐activated receptors ( PPAR) ‐γ or ‐α; Justinova et al, ; Youssef et al, ), all of which have been implemented in nicotine‐related behaviours (Justinova et al, ; Krause et al, ; Merritt et al, ) and food consumption (Fu et al, ; King et al, ). Thus, our findings of attenuating effects of BCP on nicotine and food self‐administration in CB2‐KO mice might be partly explained by BCP‐induced inhibition of FAAH or stimulation of PPAR/μ opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is unknown which non‐CB 2 receptor mechanisms are responsible for BCP‐induced reductions in nicotine or food self‐administration. Among potential non‐CB 2 receptor targets are fatty acid amide hydrolase (FAAH; Chicca et al, ), the major eCB degrading enzyme (Chicca et al, ), μ opioid receptors(Katsuyama et al, ; Paula‐Freire, Andersen, Gama, Molska, & Carlini, ), and peroxisome proliferator‐activated receptors ( PPAR) ‐γ or ‐α; Justinova et al, ; Youssef et al, ), all of which have been implemented in nicotine‐related behaviours (Justinova et al, ; Krause et al, ; Merritt et al, ) and food consumption (Fu et al, ; King et al, ). Thus, our findings of attenuating effects of BCP on nicotine and food self‐administration in CB2‐KO mice might be partly explained by BCP‐induced inhibition of FAAH or stimulation of PPAR/μ opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The stress protocol increased both ACTH and cortisol, though only ACTH showed a blunted response. A recent study of 20 smokers used a crossover design to determine changes in experimentally-induced craving and blood levels of cortisol, ACTH, and prolactin in response to a 1.6mg or 3.2mg naltrexone challenge (60). Experimental procedures consisted of 4-hour induced abstinence followed by challenge with naltrexone or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Although blocking the α4β2, but not α7 subtype has been shown to be effective in reducing nicotine intake in animal studies, blocking the α7, but not α4β2 isoform of the nicotinic acetylcholine receptors reversed cue-triggered nicotine relapse behavior ( 113 ). Current studies have developed tobacco cessation medications in addition to those summarized in the results section, such as naloxone ( 114 ) which has mostly been found to reduce craving. Franklin et al ( 45 ) found that varenicline diminished smoking cue-elicited ventral striatum and mOFC responses, and Ketcherside et al ( 8 ) found that baclofen mitigates the reward response to smoking cues through an increase in tonic activation of the DLPFC, an executive control region, and the aforementioned altered neural activity correlated with cue-induced craving.…”
Section: Discussionmentioning
confidence: 99%
“…The cue-reactivity paradigms as the primary means of eliciting smoking craving in experiments shows significant variability in the reviewed articles, reducing the cross-sectional comparability of the effects of various tobacco cessation treatment experiments. The materials used by researchers to stimulate smoking cravings were homemade ( 7 ) or modified from other researchers’ galleries ( 35 ), from tobacco ads 1 ( 114 ), queried from google images for ‘positive smoking’ and ‘negative smoking’ ( 133 ) or other sources such as the Normative Appetitive Picture System (NAPS) ( 134 ) or the International Smoking Image Series (ISIS) ( 135 ). Most home-grown stimulated smoking craving images are used for their own experiments, making it difficult to conduct replicated studies.…”
Section: Discussionmentioning
confidence: 99%